Are There Any Specific EEG Findings in Autoimmune Epilepsies?. (July 2016) - Baysal-Kirac, Leyla; Tuzun, Erdem; Altindag, Ebru; Ekizoglu, Esme; Kinay, Demet; Bilgic, Basar; Tekturk, Pinar; Baykan, Betul
This study evaluated the EEG findings of patients whose seizures were associated with a possible autoimmune etiology. Our aim was to find clues to distinguish patients with antineuronal antibodies (Ab) through EEG studies. We reviewed our database and identified antineuronal Ab positive epilepsy patients with or without autoimmune encephalitis. These patients had Abs to N -methyl-d -aspartate receptor (NMDAR) (n = 5), glycine receptor (GLY-R) (n = 5), contactin-associated protein-like 2 (CASPR-2) (n = 4), uncharacterized voltage-gated potassium channel complex (VGKC) antigens (n = 2), glutamic acid decarboxylase (GAD) (n = 2), Hu (n = 1), and amphiphysin (n = 1). The control group consisted of 21 seronegative epilepsy or encephalopathy patients with similar clinical features. EEG findings were compared between the groups in a blindfolded design. We did not find any significant difference in EEG findings between antineuronal Ab positive epilepsy patients and seronegative control group. It was remarkable that four seropositive but none of the seronegative patients presented with nonconvulsive status epilepticus (NCSE) or focal motor status epilepticus. Continuous theta and delta rhythms were observed in 5 (71%) seropositive patients with autoimmune encephalitis and 2 (25%) seronegative patients. Eight (40 %) seropositive patients showed a frontal intermittent rhythmic delta activity (FIRDA) pattern as opposed to 5 (24%) seronegative patients. Two patients with NMDAR Ab positivity showed rhythmic delta waves superimposed with beta frequency activity resembling "delta brush" pattern. EEG seems as a limited diagnostic tool in differentiating epilepsy and/or encephalopathy patients with a possible autoimmune etiology from those without. However, antineuronal Abs associated with encephalitis should be considered in the etiology of status epilepticus forms. A possible autoimmune etiology for seizures may be considered in the presence of continuous slow waves, FIRDA, and delta brush pattern in the EEG.